Pengaruh Red Flags, Independensi, Dan Skeptisme Profesional Terhadap Kemampuan Auditor Dalam Mendeteksi Fraud - Fikri Amrullah Achmad; Septemberizal Galib (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This purpose of this study to analyze: (1) The Effect of Red Flags on Auditor's Ability to Detect Fraud, (2) The Effect of Independence on Auditor's Ability to Detect Fraud, (3) The Effect of Professional Skepticism on Auditor's Ability to Detect Fraud, (4) The Effect of Red Flags, Independence, and Professional Skepticism on Auditor's Ability to Detect Fraud. This research is included in the type of quantitative research. The data method used is primary data with a survey method. The technique used is by distributing questionnaire to 79 respondents or external auditor who work at the Public Accounting Firm in the South Jakarta area. The sampling technique used is non- probability sampling and by using a convenience technique. This test uses the SmartPLS 3 technique as a data analysis tool The results of this study indicate that (1) Red Flags have a positive and significant effect on Auditor's Ability to Detect Fraud, (2) Independence have a positive and significant effect on Auditor's Ability to Detect Fraud, (3) Professional Skepticism have a positive and significant effect on Auditor's Ability to Detect Fraud, (4) Red Flags, Independence, and Professional Skepticism have a positive and significant effect on Auditor's Ability to Detect Fraud.